The Effect of Liraglutide on Weight Loss in Women with Polycystic Ovary Syndrome: An Observational Study - Rasmussen, Christina B.; Lindenberg, Svend (Frontiers in Endocrinology, 2014)
Objective: The aim of the present study was to evaluate the effect of the glucagon-like peptide-1 analog liraglutide on weight loss in overweight and obese women with polycystic ovary syndrome (PCOS). Methods: In an observational study, 84 overweight or obese women with PCOS were treated with liraglutide. Baseline characteristics and weight changes at clinical follow-up were recorded. Main outcome measures were absolute and relative weight loss. Results: In overweight or obese women with PCOS treated with liraglutide for a minimum of 4 weeks, a mean weight loss of 9.0 kg (95% CI: 7.8–10.1, p < 0.0001) and a mean decrease in BMI of 3.2 kg/m2 (95% CI: 2.8–3.6, p < 0.0001) were found. A weight loss of more than 5 and 10% of baseline weight was seen in 81.7 and 32.9% of patients, respectively. The mean duration of treatment with liraglutide was 27.8 weeks (SD 19.2). Conclusion: Treatment with liraglutide in combination with metformin and lifestyle intervention resulted in a significant weight loss in overweight and obese women with PCOS, indicating that liraglutide may be an effective alternative for weight loss in this group of patients. However, larger placebo-controlled studies are needed to confirm this.